Psychological capital dan kepuasan kerja sebagai anteseden organizational citizenship behavior pada tenaga pendidik - Albert Kurniawan Purnomo (Universitas Kristen Maranatha, 2019)
The purpose of this study is to identify the factors that encourage Organizational Citizenship Behavior (OCB) educators. Two independent variables can be identified are Pschological Capital and Satisfaction. Pschological Capital contributes the most influence to Organizational Citizenship Behavior (OCB). If the educators have been satistied, OCB will be created in the college environment. Data analysis is using SEM technique with WarpPLS 6.0 software. The target of this research was expected to educators able to run collaboration and cooperation in teaching, research, and community service, ultimately able to improve college performance. The result of this research Pschological Capital and Satisfaction direct effect to Organizational Citizenship Behavior (OCB), but no indirect effect Pschological Capital to Organizational Citizenship Behavior (OCB).